(untitled) (Journal of Mathematical Study, 2019)
The concept of minimality is generalized in different ways, one of which is the definition of k-minimality. In this paper k-minimality is studied for minimal hypersurfaces of a Euclidean space under different conditions on the number of principal curvatures. We will also give a counterexample to L_k-conjecture.